37 Optical coherence tomography tissue coverage and characterization by grey-scale signal intensity analysis post bifurcation stenting with new generation bioabsorbable polymer everolimus-eluting stents. (5th October 2017) - Hussein, H; Rai, H; Colleran, R; Xhepa, E; Sinieck, S; Cassese, S; Joner, M; Kastrati, A; Byrne, RA; Foley, D
Abstract : Introduction: Bifurcation stenting has historically been associated with higher rates of adverse clinical events. Optical coherence tomography (OCT) surveillance including grey-scale signal intensity (GSI) analysis provides information on vessel wall healing and can differentiate mature from immature tissue coverage after stent implantation. We sought to evaluate OCT-assessed healing of a novel thin-strut bioresorbable polymer everolimus-eluting stent after 3–6 months post bifurcation stenting. Methods: Patients receiving bifurcation stenting with a planned two-stent approach using a thin-strut bioresorbable polymer everolimus-eluting stent and having an OCT surveillance data collected at 3–6 months post stenting follow-up were included in this study. OCT was performed using commercially-available frequency domain OCT imaging system. Raw data of OCT image acquisitions were collected and sent to a centralized core laboratory. Morphometric analysis of contiguous cross-sections was performed at 1 mm longitudinal intervals within the stented segment (QIvus 3.0.26.0 software). GSI analysis of tissue overlying stent struts was also performed. For each cross-section, the neointimal region of interest (ROI) above each covered stent strut was delineated and 256-level GSI was measured for every pixel within the ROI (Image J software). Tissue coverage was classified as mature or immature according to a standard cut-off values derived from prior published studies (91.6 if strut calibration, 109.7 if guidewire calibration). Results: Data on a total of 31 vessels from 17 treated patients was available at a median of 5 months post stenting. Morphometric analysis revealed the mean length of stented segments to be 27.68 ±16.35 mm. The mean minimum lumen area was 5.97 ±2.97 mm ² while the minimum stent area was 6.67 ±2.63 mm ². Average lumen area was 8.27 ±2.97 mm 2 while the average stent area was 9.02 ±2.95 mm 2 . The total number of frames assessed was 869, with a total of 9, 975 visible struts. Overall strut coverage was 96.93%, while 0.34% of struts were malapposed. The mean thickness of neointimal coverage was 101.47 ±42.16µm, while the mean neointimal area was 0.75 ±0.49 mm 2 and the mean percentage stenosis 9.18±7.45%. A total of 28 lesions and 7, 971 neo-intimal regions of interest (ROIs) were assessed using GSI analysis. The mean GSI score was 95.11. A total of 53.79% of ROIs were classified as mature. Scatter plot of the GSI scores is depicted in Figure 1, Panel A, while the distribution of immature and mature ROIs is displayed in Figure 1, Panel B. Conclusions: At 3–6 months after implantation of thin-strut bioresorbable polymer EES in bifurcation lesions using a planned two stent approach, antirestenotic efficacy was high and rates of uncovered and malapposed struts was low. GSI analysis showed that more than half of neointimal areas analysed were classified as mature in keeping with well advanced vessel healing.